PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), LOAN TO DEPOSIT RATIO (LDR), RETURN ON ASSET (ROA) DAN NET INTEREST MARGIN (NIM) TERHADAP PERTUMBUHAN LABA (Studi Empiris Pada Perusahaan Perbankan Indonesia Periode 2011-2015) - Sustari Alamsyah (COMPETITIVE, 2018)
This research is to know and analyze the influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), Return On Asset (ROA), And Net Interest Margin (NIM) On Growth Income. the design of the study is causal with the unit of analysis is the company's adage of the samples taken by purposive sampling technique on the population of banking companies listed on the BEI in 2011-2015. The analysis technique used is multiple linear regression with the help of SPSS 22.0 and hypothesis test using t test. The results showed that partially CAR and LDR affect the profit growth. while NPL, ROA, and NIM have no effect on profit growth. CAR, LDR, NPL, ROA and NIM variables are simultaneously influential to profit growth. Keyword : Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), Return On Asset (ROA), And Net Interest Margin (NIM) On Growth Income